Civilizing America: Manners and Civility in American Literature and Culture - Ramanan, Mohan (Miscelánea: A Journal of English and American Studies, 2012)
Dietmar Schloss, ed.Heidelberg: Universitatsverlag Winter. American Studies. A Monograph Series. Vol. 178, 2009.